2016
DOI: 10.1177/1521025115606452
|View full text |Cite
|
Sign up to set email alerts
|

Factors Impacting the Likelihood of Student Withdrawals in Core Business Classes

Abstract: The course withdrawal decision includes both monetary and time costs for the student. Institutional costs include the misallocation of scarce seats to noncompleting students. Understanding the course withdrawal decision process can aid advisors and administrators as they seek ways to improve retention and progression. This study uses 21,318 course outcomes from introductory business core courses for the period 2003 to 2013. Our results suggest a higher withdrawal probability for students with merit-based schol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 9 publications
1
17
1
Order By: Relevance
“…Analyzing survey responses from 204 Kansas State University students who had dropped one or more courses, Reed (1981) found students were more likely to drop elective courses than required coursework. Studies of four-year (Boldt et al, 2015) and community college (Jaggars, Edgecombe, & Stacey, 2013;Jaggars & Xu, 2010;Xu & Jaggars, 2011) students have found that fully online courses have higher withdrawal rates than face-to-face courses. In Washington State's community and technical college system, online courses had a completion rate 5.5% lower (Xu & Jaggars, 2011).…”
Section: How Prevalent Is Course Dropping?mentioning
confidence: 99%
See 4 more Smart Citations
“…Analyzing survey responses from 204 Kansas State University students who had dropped one or more courses, Reed (1981) found students were more likely to drop elective courses than required coursework. Studies of four-year (Boldt et al, 2015) and community college (Jaggars, Edgecombe, & Stacey, 2013;Jaggars & Xu, 2010;Xu & Jaggars, 2011) students have found that fully online courses have higher withdrawal rates than face-to-face courses. In Washington State's community and technical college system, online courses had a completion rate 5.5% lower (Xu & Jaggars, 2011).…”
Section: How Prevalent Is Course Dropping?mentioning
confidence: 99%
“…The factors leading to college attrition are not identical to the factors that lead to course attrition (Dunwoody & Frank, 1995;Reed, 1981). Only a handful of studies, however, have applied a theoretical or conceptual framework to specifically understand students' decisions to withdraw from a course (Adams & Becker, 1990;Boldt et al, 2015;Bosshardt, 2004;Hagedorn et al, 2007;Rownd et al, 1981). Some studies extend the work of Tinto (1987) and focus more broadly on students' ability or intent to complete college.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations